1.5 mu m and visible up-conversion emissions in Er3+/Yb3+ co-doped tellurite glasses and optical fibers for photonic applications - Manzani, Danilo [UNESP]; Ferrari, Jefferson Luis; Polachini, Ferminio Cesar [UNESP]; Messaddeq, Younes [UNESP]; Lima Ribeiro, Sidney Jose [UNESP] (Royal Soc Chemistry, 2012)
Glasses with base composition (in mol%) 70TeO(2)-15GeO(2)-5K(2)O-10Bi(2)O(3) were prepared by the melt-quenching method. Er3+/Yb3+-doped and non-doped glass compositions were used as core and cladding, respectively, in the preparation of optical fibers through the sucking method. Infrared emission at 1550 nm and up-conversion emission in the visible range under 980 nm pumping are reported for glasses and optical fibers. A relatively large (Delta lambda = 91 nm) bandwidth was observed for the Er3+ 1550 nm emission. Up-conversion luminescence was observed and evaluated as a function of pump power at 980 nm. The efficient emission in the visible and infrared ranges makes this optical fiber potentially useful for amplifier and laser applications in photonics.